2017
DOI: 10.1212/wnl.0000000000003538
|View full text |Cite
|
Sign up to set email alerts
|

New-onset seizure in HIV-infected adult Zambians

Abstract: Objective: To identify the etiology of new-onset seizure in HIV-infected Zambian adults and identify risk factors for seizure recurrence.Methods: A prospective cohort study enrolling HIV-infected adults with new-onset seizure within 2 weeks of index seizure obtained clinical, laboratory, and neuroimaging data to determine seizure etiology. Participants were followed to identify risk factors for seizure recurrence. Risk factors for mortality were examined as mortality rates were unexpectedly high.Results: Eight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 22 publications
2
26
0
Order By: Relevance
“…In a prospective study in Zambia[ 38 ], HIV infected patients with a new onset of seizures were enrolled and underwent CSF testing within two weeks of the index seizure. Three patients had a reactive serum RPR and TPHA, but no individual had a positive CSF VDRL.…”
Section: Resultsmentioning
confidence: 99%
“…In a prospective study in Zambia[ 38 ], HIV infected patients with a new onset of seizures were enrolled and underwent CSF testing within two weeks of the index seizure. Three patients had a reactive serum RPR and TPHA, but no individual had a positive CSF VDRL.…”
Section: Resultsmentioning
confidence: 99%
“…This differs from our approach which retrospectively reviewed all the patients that presented to our HIV neurology clinic and then investigating possible risk factors that may have contributed towards those who developed developing seizures. Another relevant study is the ongoing Cohort of HIV-associated Seizure and Epilepsy (CHASE) study which continues to provide important new data on the epidemiology underlying epilepsy in HIV-infected Zambian population [29]. While this study is exclusively recruiting adults, it does show similarities to our study in that aetiology of epilepsy in HIV-infected patients appears to be similarly caused by infections, usually in patients with advanced HIV disease.…”
Section: Discussionmentioning
confidence: 76%
“…we also found that intital OIs (HR=4.910) and age (HR=1.336) predicted for LTFU or death in HIV patients. In other studies, the overall prevalence of OIs among HIV/AIDS patients on ART was 32.5-48% [76,77], OIs that emerge very early after ART also confer an increased risk of early mortality [78].Besides, the impact of age on HIV patients has always been a topic.An exaplanation for this trend may be that older patients have poorer immunological responses than their younger counterparts [79]. Furthermore, successful ART has led to a growing number of older HIV-1-infected individuals who face both age-related and HIV-1-related inflammation, which may synergistically promote physical decline [80,81].We also found that HBV co-infection had no effect on HIV patients' loss of follow-up or death [4,32,56].…”
Section: Discussionmentioning
confidence: 99%